Relationships between chronic pain, quality of life and war-related chronic posttraumatic stress disorder - Braš, Marijana (2008)
Introduction: Among the multitude of problems presented by patients with chronic posttraumatic stress disorder (PTSD), persistent pain in the musculoskeletal system is recognized as one of the most frequent physical complaints. However, there is no empirical studies investigating theoretical models to explain comorbidity nor well-controlled studies investigating the efficacy of treatments. Objective: The authors analysed interrelationships between chronic pain, chronic PTSD and quality of life in Croatian war veterans. Methods: The 136 veterans who were treated at the Clinic for Psychological Medicine in University Hospital Centre Zagreb during year 2007 were selected as the sample for this study.On the base of medical records, interviews and different self reported questionnaires (Mississippi Scale for combat-related PTSD, Impact of Event Scale, Mc Gill Pain Questionnaire, Pain Outcomes Questionnaire, Brief Pain Inventory, Beck Depression Inventory, Quality Of Life Questionnaire) the authors analysed the interrelationships between chronic pain, quality of life and chronic PTSD, as well as pahracotherapeutical approaches that were used in the treatment. Results: Patients suffered from different chronic pain syndromes (mostly low back pain and headaches). Affective component of pain were significantly correlated with the level of PTSD symptoms. Intrusive symptoms of PTSD were significantly related to pain intensity and pain disability. Comorbid depressive symptomatology were correlated with higher pain scores. PTSD symptoms were highly negatively correlated to quality of life, especially in the patients with chronic PTSD and comorbid chronic pain. Conclusion: We assume that chronification of stress disorder has a similar pattern of genesis in relation to acute stress stimuli as well as chronic pain syndrome in relation to peripheric painful stimulus. In both cases hypersensitivity occurs changing patients' perception of the world and causing reaction to a non-noxious stimulus. Interrelationship between chronic pain and PTSD requires a multidisciplinary approach to the assessment and treatment of patients with the emphasis on rational polipharmacy and psychotherapeutical interventions.